Acute polymicrobial airway infections: analysis in cystic fibrosis mice. Issue 1 (25th January 2023) - Lindgren, Natalie R.; McDaniel, Melissa S.; Novak, Lea; Swords, W. Edward
Abstract : Cystic fibrosis (CF) is a genetic disorder affecting epithelial ion transport, which among other impacts results in defective mucociliary clearance and innate defenses in the respiratory tract. Consequently, people with CF experience lifelong infections of the respiratory mucosa that are chronic and polymicrobial in nature. Young children with CF are initially colonized by opportunists like nontypeable Haemophilus influenzae (NTHi), which normally resides within the microbiome of the nasopharynx and upper airways and can also cause infections of the respiratory mucosa that include bronchitis and otitis media. NTHi is typically supplanted by other microbes as patients age; for example, people with CF are often chronically infected with mucoid strains of Pseudomonas aeruginosa, which prior work in our laboratory has shown to promote colonization and persistence by other opportunists that include Stenotrophomonas maltophilia . Our previous work has shown that polymicrobial infection impacts host colonization and persistence of incoming microbes via diverse mechanisms that include priming of host immunity that can promote microbial clearance, and cooperativity within polymicrobial biofilms, which can promote persistence. In infection studies with BALB/c Cftr tm1UNC mice, results showed, as previously observed for WT BALB/c mice, preceding infection with NTHi decreased colonization and persistence by P. aeruginosa . Likewise, polymicrobial infection of BALB/c Cftr tm1UNC and C57BL/6 Cftr tm1UncTg (FABPhCFTR)1Jaw/J mice showed correlation between S. maltophilia and P. aeruginosa, with increased bacterial colonization and lung pathology. Based on these results, we conclude that our previous observations regarding polymicrobial infections with CF opportunists in WT mice are also validated using CF mice.